(untitled) (International Journal of Medical and Surgical Sciences, 2020)
Anthropometric studies began as a methodology in biological anthropology for comparing of the anthropological features of the today’s nations and previous nations too, as well as in screening and diagnosing of malnutrition. It is evident that a large number of studies have been performed on measures of body height, weight, trunk and limb dimensions, subcutaneous fatness and body composition, etc., but less attention has been paid to cephalofacial measurements. The purpose of this research was to study and explain the latent structure of the humans’ cephalofacial variables. On 754 healthy entities (561 male entities and 193 female entities), aged 18-35 years, were measured 11 cephalofacial variables. The collected data were analyzed through descriptive parameters, Correlation analysis, and Factorial analyses. Correlation analysis confirms the existing of some variables’ sets, which are characterized with the higher correlations between variables within the set. Through the principal component analysis of the Factor Analysis (rotation method direct obliging, Keiser criterion) were extracted four latent factors which explain 66.39 % of the total variance: Factor of intracranial capacity; Transversal factor of the face; Longitudinal factor of the face. Conclusion: The composition of the extracted factors was compatible with the scientific explanation of the anthropologists regarding the development of the head.